Double balloon enteroscopy in the detection and removal of jejunal anisakiasis: Case report - Erika Abe; Tsukasa Ishida; Tatsuya Osuga; Saori Kakuyama; Hirofumi Ogawa; Katsutoshi Nabeshima (DEN Open)
Abstract A 53‐year‐old Japanese man presented to the emergency department with epigastric pain and bloating. Computed tomography revealed a thickening of the jejunal wall and proximal dilation. Double‐balloon enteroscopy was performed to investigate the jejunal thickening, which revealed an anisakis larva in the jejunum with an associated ulcer. The larva was removed using endoscopic forceps, after which there was immediate improvement of symptoms. Further patient interview determined that he had consumed marinated mackerel the day before the onset of symptoms. After diagnosis of small intestinal anisakiasis, he was successfully treated using double‐balloon enteroscopy. Its use for small intestinal anisakiasis is rare, and this case may be the first instance in the jejunum. Removal of the anisakis larva led to a clear diagnosis and a quick resolution of symptoms. A history of raw fish consumption a few days before the onset of abdominal symptoms and abnormal findings on computed tomography scans are key to the diagnosis of small intestinal anisakiasis. Double‐balloon enteroscopy was thought to be a safe means of making accurate diagnoses and appropriate treatment of our patients.